Energy-Adjusted Dietary Inflammatory Index in pregnancy and maternal cardiometabolic health: findings from the ROLO studyAJOG Global Reports at a Glance - Amy Gainfort, BSc; Anna Delahunt, PhD; Sarah Louise Killeen, PhD; Sharleen L. O'Reilly, PhD; James R. Hébert, ScD; Nitin Shivappa, PhD; Fionnuala M. McAuliffe, MD (Elsevier, 2023)
Background: Excessive inflammation during pregnancy has been linked to adverse long-term health outcomes for both mothers and their children. One such outcome is maternal cardiometabolic dysfunction. The Energy-Adjusted Dietary Inflammatory Index is a method of scoring the overall inflammatory potential of the diet. Research on how the inflammatory potential of the maternal diet during pregnancy affects maternal cardiometabolic factors is limited. Objective: We investigated if the maternal Energy-Adjusted Dietary Inflammatory Index was associated with maternal cardiometabolic factors during pregnancy. Study design: This is a secondary analysis of 518 individuals who participated in the ROLO (Randomized cOntrol trial of a LOw glycemic index diet in pregnancy) study. Maternal Energy-Adjusted Dietary Inflammatory Index scores were calculated in early (12-14 weeks' gestation) and late pregnancy (34 weeks' gestation) using data collected from 3-day food diaries. Body mass index, blood pressure, fasting lipid profiles, glucose levels, and HOMA1-IR were obtained in early and late pregnancy. Multiple linear regression examined associations between early-pregnancy Energy-Adjusted Dietary Inflammatory Index and early and late maternal cardiometabolic markers. In addition, the relationship between late-pregnancy Energy-Adjusted Dietary Inflammatory Index and late cardiometabolic factors was explored. Regression models were adjusted for maternal ethnicity, maternal age at delivery, education level, smoking status, and original randomized control trial group allocation. In regression models examining late-pregnancy Energy-Adjusted Dietary Inflammatory Index with late lipids, change in lipid level from early to late pregnancy was also adjusted for. Results: Women's mean (standard deviation) age at delivery was 32.8 (±4.01) years, with median (interquartile range) body mass index of 24.45 (23.34-28.20) kg/m2. Mean (standard deviation) Energy-Adjusted Dietary Inflammatory Index was 0.59 (±1.60) in early pregnancy and 0.67 (±1.59) in late pregnancy. In adjusted linear regression analysis, first-trimester maternal Energy-Adjusted Dietary Inflammatory Index was positively associated with maternal body mass index (B=0.007; 95% confidence interval, 0.003-0.011; P=.001), early-pregnancy cardiometabolic markers including total cholesterol (B=0.155; 95% confidence interval, 0.061-0.249; P=.001), triglycerides (B=0.043; 95% confidence interval, 0.005-0.080; P=.03), low-density lipoproteins (B=0.129; 95% confidence interval, 0.049-0.209; P=.002), and diastolic blood pressure (B=0.538; 95% confidence interval, 0.070-1.006; P=.02), and late-pregnancy cardiometabolic markers including total cholesterol (B=0.127; 95% confidence interval, 0.012-0.243; P=.01) and low-density lipoproteins (B=0.110; 95% confidence interval, 0.010-0.209; P=.03). In the third trimester, Energy-Adjusted Dietary Inflammatory Index was associated with late-pregnancy diastolic blood pressure (B=0.624; 95% confidence interval, 0.103-1.145; P=.02), HOMA1-IR (B=0.030; 95% confidence interval, 0.005-0.054; P=.02), and glucose (B=0.003; 95% confidence interval, 0.003-0.034; P=.03). No associations were observed between third-trimester Energy-Adjusted Dietary Inflammatory Index and late-pregnancy lipid profiles. Conclusion: Maternal diets with a higher Energy-Adjusted Dietary Inflammatory Index, which were low in anti-inflammatory foods and rich in proinflammatory foods, were associated with increased levels of cardiometabolic health risk factors in pregnancy. Promoting dietary intakes that have a lower inflammatory potential may support more favorable maternal cardiometabolic profiles during pregnancy.